Potensialitas dan keterbatasan inovasi morfologis dalam bahasa Indonesia; Contoh kombinasi afiks "keter-/-an" - Samuel, Jérôme (Wacana, Journal of the Humanities of Indonesia, 2009)
This paper examines with a particular affixe (keter-/-an) consisting in two primary affixes. Through the analyse of terms coined by the Pusat Bahasa and spontaneous terms, the paper distinguishes between "double" and "complex" affixation, corresponding to different operating modes of affixation. The first deals with an already affixed and lexicalized word, then reaffixed and relexicalized. The second, almost only found in documents produced by the Pusat Bahasa, refers to a base getting a first affix in a poorly (or not) lexicalized form, constituting no more than a morphological stage towards the wished form, which is intent as lexicalized. Complex affix keter-R-an is basically a morphological calque and the author argues that it has been promoted and used during New Order on an ideological basis, as a mean to modernize Indonesian terminology by keeping its shape indigenous rather than by direct borrowing of English terms.